2020
DOI: 10.1111/liv.14392
|View full text |Cite
|
Sign up to set email alerts
|

Genetic variants of innate immunity receptors are associated with mortality in cirrhotic patients with bacterial infection

Abstract: Background & Aims Acute‐on‐chronic liver failure (ACLF) is characterized by acute decompensation of cirrhosis (AD), organ failure(s) and high risk of short‐term mortality with bacterial infection frequently as precipitating event. Innate immune pattern recognition receptors and members of the lectin pathway of complement activation are crucial to the innate immune response to pathogens. The aim of this study was to investigate whether single nucleotide polymorphisms (SNPs) of innate immune components are assoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…For example, single-nucleotide variants might modulate the release of inflammatory molecules by innate immune cells or might induce changes in the expression of PRRs, such as TLRs. Consistent with this, genetic variants in genes coding for receptors of the innate immune system such as nucleotide-binding oligomerization domain 2 (NOD2) or ligands as mannan-binding lectin (MBL) and MBL-associated serine proteases (MASP) 2 have been shown to associate with increased short-term mortality in AD and ACLF patients [13]. Moreover, single nucleotide polymorphisms within the IL-1 gene cluster have been reported to protect patients with AD cirrhosis from uncontrolled systemic inflammation and to reduce the predisposition of these patients to develop ACLF [14].…”
Section: Systemic Inflammation and Immunopathology Are Major Drivers mentioning
confidence: 77%
“…For example, single-nucleotide variants might modulate the release of inflammatory molecules by innate immune cells or might induce changes in the expression of PRRs, such as TLRs. Consistent with this, genetic variants in genes coding for receptors of the innate immune system such as nucleotide-binding oligomerization domain 2 (NOD2) or ligands as mannan-binding lectin (MBL) and MBL-associated serine proteases (MASP) 2 have been shown to associate with increased short-term mortality in AD and ACLF patients [13]. Moreover, single nucleotide polymorphisms within the IL-1 gene cluster have been reported to protect patients with AD cirrhosis from uncontrolled systemic inflammation and to reduce the predisposition of these patients to develop ACLF [14].…”
Section: Systemic Inflammation and Immunopathology Are Major Drivers mentioning
confidence: 77%
“…Similarly, host genetic factors, for instance, single nucleotide variants might modulate the release of inflammatory mediators by innate immune cells and can change the expression of pattern recognition receptors (PRRs). Genetic variations in genes coding for innate immune receptors including nucleotide-binding oligomerization domain (NOD)-2, mannan-binding lectin (MBL), and MBL-associated serine protease (MASP)-2 are associated with increased short-term mortality in ACLF and patients with acute decompensation ( 39 ). In addition, single nucleotide polymorphism with IL-1 gene clusters plays a protective role in patients with acute decompensated cirrhosis by controlling systemic inflammation and reducing the development of ACLF ( 40 ).…”
Section: Pathophysiological Mechanisms In Aclfmentioning
confidence: 99%
“…Polymorphisms of pattern recognition receptors, such as nucleotide-binding oligomerisation domain containing 2 (NOD2), Toll-like receptor (TLR) 2 and 4, or nuclear dot protein 52 kDa have been associated with an increased risk of bacterial infections in some studies, but this has not been confirmed by other studies. [79][80][81][82] Sodium dismutase polymorphisms, another critical enzyme in immune defence and cell damage, were associated with decompensation and risk of bacterial infections. 83 In another study, the PNPLA3 G/G genotype was associated with a 2fold increase in the risk of decompensation.…”
Section: Genetic Predispositionmentioning
confidence: 99%